(untitled) - Clark, Colin (Oxford, 1970)
This book contains the critically important facts concerning the application of water by human agency to assist the growth of crop and grass. Much scattered material has been collated into a coherent structure and a great deal of information is presented in tabular form. The many important topics carefully discussed: the water requirements of crops in various climates and soils, in particular in Africa, the Middle East, australia and America; the cost of irrigation water from streams, canals. wells, pumps and dams; water resources; charges for water; desalination
Keywords: Irrigation farming; Economic aspects